Menelusuri Integrasi Fungsi Estetika dan Etika dalam Membaca Al-Qur’an - Putri Sri Rizqi; Umi Kultsum (Jurnal Budi Pekerti Agama Islam, 2025)
The Qur’an is not only a source of law and moral guidance for Muslims but also a manifestation of harmony between aesthetics and ethics that shapes human spirituality. This study aims to explore the integration of aesthetic and ethical functions in Qur’anic recitation (tilawah), examining the relationship between the beauty of voice and the nobility of character in articulating the divine revelation. Using a descriptive qualitative method through a literature study, the research finds that the aesthetic aspect is reflected in the application of tajwid, melodic arrangement (maqamat), vocal beauty, and rhythmic harmony. Meanwhile, the ethical aspect is expressed through sincerity, humility, respectfulness in recitation, and the embodiment of Qur’anic values in daily life. The findings reveal that true beauty in Qur’anic recitation lies not merely in the pleasantness of the voice or technical mastery but in the purity of intention and spiritual depth of the reciter. The integration of aesthetics and ethics serves as a crucial foundation for nurturing spiritual depth, moral character, and cultural appreciation of the Qur’an, particularly in the context of Islamic education and da’wah. Thus, reading the Qur’an with both aesthetic and ethical awareness is not only an artistic expression but also an act of worship that unites beauty, morality, and devotion to Allah SWT in a holistic manner.